The Relationship of Lecturer’s Communication Pattern and Peer Group Communication Intensity to Learning Interest in Online - Ali Arif Setyawan*; Jahid Syaifullah (Riwayat: Educational Journal of History and Humanities, 2023)
Online learning is learning that is developed with the aim that learning can be carried out without any time and space constraints. Utilization of information technology is one of the keys to the success of online learning. However, there are also weaknesses in online learning which can reduce student interest in learning. Barriers to the ability of lecturers to communicate learning materials, communicate with students, and the togetherness of students in peer groups among them are factors that play a role in student interest in learning online. This research is a descriptive correlative research with the aim of describing the communication patterns of lecturers, the intensity of peer group communication, student interest in learning and analyzing whether or not there is a relationship between lecturer communication patterns and peer group communication intensity with student learning interests at the Universitas Surakarta (Surakarta University). The research sample was 60 students majoring in Communication at the Universitas Surakarta class of 2019 and 2020 which were determined using the proportional random sampling technique. Research data collection using a questionnaire, and data analysis using univariate and bivariate analysis using the Spearman Rank correlation test. The conclusion of the study is that there is a direct and significant relationship between lecturer communication patterns and the intensity of peer group communication with student interest in learning at the Universitas Surakarta.